Computational insights into 2-(aminooxy)butanoic acid's potential as a therapeutic agent against Alzheimer's disease and Progesterone receptor - R.T. Usha; A. Prabakaran; Uma Maheswari Chandramohan; T. Gnanasambandan (Results in Chemistry)
This study elucidates the molecular interactions and binding mechanisms of 2-(Aminooxy)butanoic acid with Alzheimer's disease-related acetylcholinesterase (AChE) and progesterone receptor (PR) proteins. Utilizing advanced computational approaches, including density functional theory with dispersion correction (DFT-D3) and molecular dynamics (MD) simulations, along with MMPBSA calculations, we investigated the molecular recognition, potential energy landscapes, and geometrical parameters governing ligand-protein interactions. Non-covalent interactions were characterized using reduced density gradient (RDG) analysis, revealing key hydrophobic and electrostatic interactions. Molecular docking and simulation studies identified critical residues involved in ligand-protein binding, demonstrating the stability of AChE and PR complexes. The comparative analysis of protein-ligand interaction energies using MMPBSA highlighted the strong binding affinity between 2-(Aminooxy)butanoic acid and the target proteins. Our findings highlight the potential biological activity of 2-(Aminooxy)butanoic acid against Alzheimer's disease and progesterone-related disorders, including Gynecological conditions and cancer. This study showcases the predictive power of computational methods in rational drug design, providing novel insights into the molecular mechanisms underlying the bioactivity of this compound and its potential applications in pharmaceutical development.